Corals and Their Microbiomes Are Differentially Affected by Exposure to Elevated Nutrients and a Natural Thermal Anomaly - Wang, Lu; Shantz, Andrew A.; Payet, Jérôme P.; Sharpton, Thomas J.; Foster, Amelia; Burkepile, Deron E.; Vega Thurber, Rebecca (Frontiers in Marine Science, 2018)
Nutrient pollution can increase the prevalence and severity of coral disease and bleaching in ambient temperature conditions or during experimental thermal challenge. However, there have been few opportunities to study the effects of nutrient pollution during natural thermal anomalies. Here we present results from an experiment conducted during the 2014 bleaching event in the Florida Keys, USA, that exposed Agaricia sp. (Undaria) and Siderastrea siderea corals to 3 types of elevated nutrients: nitrogen alone, phosphorous alone, and the combination of nitrogen and phosphorus. Overall, bleaching prevalence and severity was high regardless of treatment, but nitrogen enrichment alone both prolonged bleaching and increased coral mortality in Agaricia corals. At the same time, the elevated temperatures increased the prevalence of Dark Spot Syndrome (DSS), a disease typically associated with cold temperatures in Siderastrea siderea corals. However, nutrient exposure alone did not increase the prevalence or severity of disease, suggesting that thermal stress overwhelms the effects of nutrient pollution on this disease during such an extreme thermal event. Analysis of 85 Siderastrea siderea microbial metagenomes also showed that the thermal event was correlated with significant shifts in the composition and function of the associated microbiomes, and corals with DSS had microbiomes distinct from apparently healthy corals. In particular, we identified shifts in viral, archaeal, and fungal families. These shifts were likely driven by the extreme temperatures or other environmental co-variates occurring during the 2014 bleaching event. However, no microbial taxa were correlated with signs of DSS. Furthermore, although nutrient exposure did not affect microbial alpha diversity, it did significantly affect microbiome beta-diversity, an effect that was independent of time. These results suggest that strong thermal anomalies and local nutrient pollution both interact and act independently to alter coral health in a variety of ways, that ultimately contribute to disease, bleaching, and mortality of reefs in the Florida Keys.